EFFECT OF DEFECT GEOMETRY IN A COMPOSITE ON RELIABILITY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This work focuses on the study of the effect of the physical properties of a random-type composite material and the geometric shape of defects on the reliability analysis of an inspection device using non-destructive testing. Two types of defect geometries are considered: rectangular and triangular. A stochastic finite element method (SFEM) was used to solve the 2D electromagnetic equation in a cylindrical structure. The differential sensor recovers the impedance change signal in the fault zone. The signal is analyzed and compared for the two types of geometries. Post-processing is started to assess the reliability of our structure by determining the reliability index and the probability of failure. The results obtained for random rectangular and triangular shapes are presented, along with a comparison between the stochastic finite element method and the Monte Carlo method. A good agreement is observed. The results show that the proposed SFEM model offers post-processing in addition to analysis, compared to the Monte Carlo method, which requires numerous draws for analysis and relies on the inverse problem to determine the actual values of the physical property considered.
Keywords: Random geometry and Property; Composite; Non-destructive testing; Stochastic finite elements; Reliability analysis